BEHAVIORAL MANAGEMENT: MOTIVATIONAL FACTORS OF EFFECTIVE LEADERSHIP - Chychun, Valentyna; Polianko, Halyna (Social Development: Economic and Legal Issues, 2025)
The article is devoted to the study of motivational factors that determine the effectiveness of leadership within the framework of the concept of behavioral management. The relevance of the topic is due to the transformation of management approaches in response to changing work priorities, digitalization of business processes and the growing importance of the emotional intelligence of the manager. In the modern organizational environment, where performance largely depends on the level of staff involvement, behavioral management factors play a decisive role in shaping the motivational climate. The purpose of the study is to identify and classify key motivational factors that determine the effectiveness of leadership in the behavioral management system, as well as to substantiate practical approaches to improving management decisions based on them. The object of the study is management activity in organizations; the subject is motivational determinants of effective manager behavior in modern conditions. The methodological basis is made up of general scientific and special methods: content analysis of scientific literature (to systematize theoretical approaches to motivation), questionnaires of management personnel (to identify the subjective perception of motivational incentives), expert survey (to assess the relevance of behavioral models of leadership), correlation analysis (to establish relationships between the behavioral characteristics of a leader and the level of motivation of employees). The collection of empirical data was carried out in the form of online surveys among middle and senior managers of Ukrainian companies in various sectors of the economy. During the study, the author performed: classification of motivational factors taking into account the behavioral characteristics of the leader; analysis of the relationship between management style and motivational performance of personnel; development of practical recommendations for adapting leadership strategies to the needs of a modern team. The conclusions show that the most effective are those leadership models that are based on a combination of emotional support, trust, autonomy and recognition of achievements. It is shown that employee motivation depends not only on material incentives, but also on the behavioral adaptability of the leader to the social context. It is proposed to implement programs for the development of emotional intelligence and behavioral coaching for managers, which will allow to strengthen the effectiveness of personnel management in conditions of dynamic changes.